A necessary engagement [ reinventing America's relations with the Muslim world - Nakhleh, Emile A. , 1938- (Princeton : Princeton University Press, 2009)
Offering a balance between analysis, personal memoir, and foreign policy remedies, this book injects much-needed wisdom into the public discussion of long-term US-Muslim relations. This title argues that an engagement with the Muslim world benefits the national interest of the United States
Political Islam and Islamization -- Intelligence, political Islam, and policymakers -- Public diplomacy : issues and attitudes -- Public diplomacy: a blueprint
Description based on print version record
Includes bibliographical references (p [151]-153) and index
Keywords: Islamic countries -- Relations -- United States; United States -- Relations -- Islamic countries